2015
DOI: 10.1016/j.ultrasmedbio.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Enamel Thickness Measurements with Ultrasound

Abstract: Ultrasound measurements showed good agreement with histology which highlights its potential for monitoring the progressive loss of enamel thickness in erosive tooth surface loss (TSL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Therefore, reliable methods capable of determining the setting process of impression material at every step of polymerization are necessary, and these measurement procedures should be performed with minimal time delay. Ultrasonic imaging is a noninvasive technique that offers considerable potential for diagnosis, is a valuable tool for research [11][12][13][14] , and allows measurement of dentin thickness 15,16) . It also allows for monitoring the setting process of impression material because the sound velocity is dependent on the elastic modulus and the attenuation coefficient correlates with the viscoelastic properties of elastomers 17,18) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reliable methods capable of determining the setting process of impression material at every step of polymerization are necessary, and these measurement procedures should be performed with minimal time delay. Ultrasonic imaging is a noninvasive technique that offers considerable potential for diagnosis, is a valuable tool for research [11][12][13][14] , and allows measurement of dentin thickness 15,16) . It also allows for monitoring the setting process of impression material because the sound velocity is dependent on the elastic modulus and the attenuation coefficient correlates with the viscoelastic properties of elastomers 17,18) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the present study used ultrasound in order to indicate when an endodontic sealer had set completely. Variations in the speed of sound passing through a sample provides information on its viscoelastic properties, so that the faster the speed of sound, the greater the density of the material (Bozkurt et al, 2005; Sindi et al, 2015; Tsujimoto et al, 2019). The method involves short ultrasonic pulses (speed 90 m/s) that pass through the sample, but do not accumulate energy in the molecules of the material.…”
Section: Discussionmentioning
confidence: 99%
“…Such properties make it possible to use Ultrasound to detect cavities and measure enamel and dentine thickness (Bozkurt et al, 2005; Matalon et al, 2007; Ng et al, 1989; Peck et al, 1989; Watanabe et al, 2004; Yasuda et al, 2007), as well as assess the mechanical properties of dental materials (Denisova et al, 2004) and the adhesive interfaces (Yasuda et al, 2007). Considering that the speed of propagation of ultrasonic waves, which occurs by converting electrical or magnetic energy into mechanical energy (Plotino et al, 2007), is greater in solids than liquids (Sindi et al, 2015), there is a potential application of this technology to determine the setting time of root canal sealers, and even more, it can be able to indicate if the sealer is completely set or not. Therefore, the present study was designed to present and explore the potential of an ultrasound‐based experimental model to determine the setting time of root canal sealers.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, several researchers carried out ultrasonic investigations on dental tissues and their results confirmed that ultrasound as tested in-vitro shows considerable promise for the assessment of tooth layers, tooth surface demineralization and types of dentin [2][3][4]. Recently, ultrasound is being used for early caries detection [5], assessment of sound dentin [6] and enamel thickness [7], visibility of pulp spaces [8], assessment of gingival thickness [9], dental implants placement [10], measurement of bone thickness surrounding implants [11] and accuracy of tooth impressions [12]. Lately, extensive reviews of ultrasound imaging advances in dentistry were published by Marotti et al [13] and Kocasarac & Angelopoulos [14].…”
Section: Introductionmentioning
confidence: 95%